Investigation of the Causes of Premature Failure of the Suspension and Brake System of Buses “Volgabus” - Popov A. V. (EDP Sciences, 2021)
The article gives a performance measurement ofthe suspension and brake system of buses “Volgabus-5270GH” on the basis of bus removals with different mileage values. Scheduled maintenance and repair system implies the elimination of buses removals and repair works between MO1 (MO - Maintenance Operations) and MO2. The authors have analysed malfunctions in the suspension and brake system. Based on many researches, it has been established that the resource of components and parts of the vehicles in kilometers of run, under proper operation, obeys the law of normal distribution. It has been determined that premature buses removals are also possible under condition of high-quality manufacturing and timely performance of maintenance with the influence of operating factors of the route network of the town Volzhsky. The analysis of bus driving modes on the main routes and their possible connection with the suspension and brake system failures has been carried out. Recommendations are given to improve the performance of the buses.